Product market competition and financial analysts' forecast quality: The mediating role of financial reporting quality - Amjad Iqbal; Fayaz Ali; Muhammad Umar; Irfan Ullah; Khalil Jebran (Borsa İstanbul Review, 2022)
We reveal the reporting quality channel by investigating the mediating role of financial reporting quality (FRQ) in the relationship between product market competition (PMC) and analysts' forecast quality (AFQ). We analyze a sample of 1179 unique nonfinancial Chinese listed firms, resulting in 6074 firm-year observations, over the period 2007-2016. We employ the Herfindahl-Hirschman Index (HHI) to measure PMC, the modified Jones model to measure FRQ, and analysts' forecast dispersion and accuracy as measures of AFQ. We then apply a three-step mediation model following the Baron and Kenny approach to test our proposed hypotheses. The results of the mediation model support our hypotheses by revealing the mediating role of FRQ in the PMC-AFQ relationship. The results suggest that intense PMC enhances the FRQ of Chinese-listed firms, in turn enhancing AFQ. Our findings present important implications for both current and potential investors, financial analysts, and relevant government regulatory bodies.
Keywords: G17; M41; 330; China; Product market competition; Financial reporting quality